Effect of calibration methods on the accuracy of angiographic measurements during transcatheter procedures in dogs. (12th March 2018) - Markovic, Lauren E.; Scansen, Brian A.
Abstract : Background: Different methods to perform reference calibration of an angiographic image exist; however, a prospective comparison of calibration methods has yet to be investigated in veterinary medicine. Objective: To compare angiographic measurements using two commonly employed reference calibration methods, an esophageal pigtail marker catheter (EC) versus a radiopaque table ruler (TR). Animals: Thirty‐five client‐owned dogs undergoing transcatheter intervention. Methods: Prospective comparison study. Two reference calibration methods, EC and TR, were recorded in dogs undergoing transcatheter procedures from May 2016 to July 2017. Relevant measurements were performed in triplicate and averaged after image calibration to either EC or TR. Comparisons between methods were made by correlation, paired t ‐test, the method of Bland and Altman, and Passing‐Bablok regression. Results: A total of 39 angiographic structures were measured. Interventions included balloon pulmonary valvuloplasty (n = 21), patent ductus arteriosus occlusion (n = 11), subaortic or sub‐pulmonary balloon dilatation (n = 4), and cor triatriatum membranostomy (n = 3). Angiographic measurements were larger when calibrated to EC versus TR ( P < .0001). The mean bias was 0.86 mm, with greater bias for larger measurements. The EC measurements were ∼10% greater than TR based on regression analysis. Weight was correlated to the difference between methods (ρ = 0.55, P = .0003). Conclusions and Clinical Importance: Angiographic image calibration using a ruler placed on the fluoroscopy table underestimates the size of a structure by ∼10% as compared with a marker catheter placed within the esophagus. This effect is greatest when measuring larger structures such as the pulmonary valve annulus and in larger dogs.